Student Engagement as a Mediator of the Relationship Between Self-Control and Truancy Behavior Among Junior High School Students - Nur Akmal; Nur Athirah Hadis (Universitas Negeri Makassar, 2026)
Abstrak. Truancy behavior is a serious problem in schools, especially in junior high school students, which can interfere with academic and social development. This study aims to determine the relationship between self-control and truancy behavior, and to test the role of student engagement as a mediator in the relationship. This study uses a quantitative correlational approach with a sample of 207 students from a public junior high school in Makassar selected through the accidental sampling technique. Data were collected using three psychological scales, namely the truancy behavior scale, the self-control scale, and the student engagement scale, which have been tested for validity and reliability. The analysis technique used is path analysis with the help of SPSS and Jamovi software. The results of the study indicate that there is a significant negative relationship between self-control and truancy behavior, and student engagement acts as a mediator in the relationship. This means that students with high self-control tend to have higher levels of learning engagement, which ultimately reduces the tendency for students to skip school. This finding provides important implications for schools and parents to develop intervention programs that can increase students self-control and engagement in order to prevent truancy behavior.